Hemostasis in endoscopic endonasal skull base surgery using the Aquamantys bipolar sealer: Technical note. (July 2017) - Bram, Richard; Fiore, Susan; McHugh, Daryl; Samara, Ghassan J.; Davis, Raphael P.
Highlights: Intraoperative hemostasis is critical during endoscopic surgery of the skull base. The Aquamantys® is a bipolar sealer which uses radiofrequency energy and saline. In this report, we describe our experience with the Aquamantys® in skull base surgery. The device provides excellent radial spread of energy while staying limited in depth. Abstract: Background: A major challenge during endoscopic transsphenoidal surgery is adequate intraoperative hemostasis. The Aquamantys® is a relatively new bipolar sealing device which uses radiofrequency energy and saline. This promotes hemostasis while decreasing charring and thermal spread. In this paper, we describe our experience with the Aquamantys® Mini EVS 3.4 Epidural Vein Sealer Bipolar Electrocautery System (Medtronic Advanced Energy, Portsmouth, NH, USA) during endoscopic surgery for tumors of the skull base with particular attention to ergonomic benefits and technical nuances. Methods: We conducted a retrospective review of all patients undergoing endoscopic surgery for skull base tumors from September 2012 to June 2016 at our institution. All procedures used the Aquamantys® system. 45 cases were identified. Results: Successful hemostasis was achieved in all cases with an average estimated blood loss (EBL) of 46 mL (Range 10–250). There were no intraoperative complications. The single-shaft design allowed for excellent manipulation compared to pistol-grip bipolar forceps. The thermal energy provided excellent radial coverage without extensive penetration into viable pituitary tissue. Conclusion: To our knowledge, this is the largest series documenting the use of the Aquamantys® system in skull base surgery. The device is easily mobile and highly effective within the endonasal corridor and should be a tool in the repertoire of the endoneurosurgeon. Randomized control trials would be useful in comparing EBL between the Aquamantys® and standard bipolar electrocautery.